Types of substance use and predictors of substance use disorders in patients suffering from psychiatric disorders - A cross sectional study - Jaafar Omer Ahmed (Industrial Psychiatry Journal)
Background: The types of substances used by psychiatric patients in Iraq and the Middle East vary from other areas of the world. In this region, patients mostly use prescribed drugs. Aim: This study aimed to investigate the types of substance use disorder (SUD) and their correlates among psychiatric patients in the Kurdistan region. Materials and Methods: The study was conducted on patients, who visited outpatient psychiatric consultation units in the Kurdistan region of Iraq within 6 months. In this study, two hundred fifty (250) adult patients of both genders diagnosed with psychiatric disorders were included. Results: Alcohol use disorder was diagnosed in 10 (4%) of cases; after that, the most commonly used substances were benzodiazepine and trihexyphenidyl, each of them positive in 7 (2.8%) of cases, followed by opiates in 4 (1.6%) cases and poly substances in 2 (0.8%) of the cases. The correlates of SUDs included male gender, divorced person, higher educational level, and being employed. Conclusion: Psychiatric patients mostly use prescribed medications, especially benzodiazepines and trihexyphenidyl. Future research will be required to study the comorbidity between psychiatric disorders and SUDs in various groups and different settings.